Screening Of Some Chilli Cultivars For Their Resistance Against Meloidogyne Incognita - ABHINITI MALHOTRA,; TRIPTI AGARWAL,; P. C. TRIVEDI, (International Journal of Pharma and Bio Sciences, 2012)
Five cultivars of chilli, Capsicum annuum, were screened for resistance against Meloidogyne incognita in pot experiments. Three-week-old seedlings were inoculated with 1000 freshly hatched juveniles of M. incognita. Ninety days after inoculation the plants were uprooted and examined for galls, root and shoot lengths, fresh/dry root and shoot weights. The cultivar Pusa Jwala was assessed as moderately resistant with the minimum number of galls and variety PC-1 was highly susceptible developing the maximum number of galls. All the other varieties exhibited variable degree of susceptibility between Pusa Jwala and PC-1.